A rapid hemostasis for incompressible wounds by microwave-assisting construction of cellulose sponge with chitosan. (September 2022) - Fan, Xialian; Xue, Rong; Li, Na; Yang, Qian; Yu, Chuan; Dong, Yichen; Li, Yijin; Tang, Keyong; Wan, Guangming
Graphical abstract: Highlights: Incompressible bleeding wounds can achieve hemostasis within 39 s under the action of hemostatic sponge. Cellulose sponge with rich pore structure is prepared by the combined method of microwave and foaming. The composite sponge has fast water absorption rate and shape recovery ability. Abstract: Rapid hemostasis in incompressible wounds using cellulose sponge, coupled with environmentally friendly and low-cost preparation, remains a challenge. Herein, cellulose sponges loaded with chitosan with abundant rich pore structure and high water absorption capacity were prepared with cellulose carbamate by using gas foaming method. Animal experiments showed that the blood loss and hemostasis time can be significantly shortened from 225 s to 39 s by the plug the incompressible wound using adaptable composite sponges. Scanning electron microscope results showed that the chitosan formed a porous network structure on the surface and between the pores of the cellulose sponge. An obvious inhibitory effects of composite sponge on Escherichia coli and Staphylococcus aureus could effectively reduce wound infection. And the rapid shape recovery ability of the composite sponge was beneficial to sealing the bleeding wound quickly. The results of in vitro hemolytic activity, cytotoxicity and live-dead cell staining showed the composite hemostatic sponges have excellent biocompatibility. In particular, the preparation of cellulose sponge by microwave-assisted method can effectively improve the environmental pollution and cumbersome steps caused by current industrial production. It is expected to be used for rapid hemostasis of non-compressible hemorrhagic wounds.